2022
DOI: 10.1186/s13063-022-06391-w
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol to test the efficacy of self-administration of dexmedetomidine sedative therapy on anxiety, delirium, and ventilator days in critically ill mechanically ventilated patients: an open-label randomized clinical trial

Abstract: Background Administration of sedative and opioid medications to patients receiving mechanical ventilatory support in the intensive care unit is a common clinical practice. Methods A two-site randomized open-label clinical trial will test the efficacy of self-management of sedative therapy with dexmedetomidine compared to usual care on anxiety, delirium, and duration of ventilatory support after randomization. Secondary objectives are to compare sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Timely introduction of specific agents that may promote weaning, reduce agitation and delirium will facilitate early weaning and liberation from mechanical ventilation [ 38 ]. Moreover, new insights in relation of sedation with personalized care may be provided by trials evaluating the efficacy of patient-controlled sedation to manage symptoms associated with the distress induced by mechanical ventilation [ 39 ]. Sedation trials in the future need to incorporate non-pharmacological interventions as part of integrated approach to optimal sedation, anxiolysis and delirium management.…”
Section: Overcoming Sedation Challengesmentioning
confidence: 99%
“…Timely introduction of specific agents that may promote weaning, reduce agitation and delirium will facilitate early weaning and liberation from mechanical ventilation [ 38 ]. Moreover, new insights in relation of sedation with personalized care may be provided by trials evaluating the efficacy of patient-controlled sedation to manage symptoms associated with the distress induced by mechanical ventilation [ 39 ]. Sedation trials in the future need to incorporate non-pharmacological interventions as part of integrated approach to optimal sedation, anxiolysis and delirium management.…”
Section: Overcoming Sedation Challengesmentioning
confidence: 99%
“…Lastly, the ‘Patient-controlled comfort measures’ have integration of customizable environmental and comfort controls. This allows patients to personalize their immediate surroundings, influencing factors like lighting and noise levels, contributing to a more comfortable and healing-oriented environment including pain and sedation control[ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients must follow simple commands, be able to use a medication push-button infusion device, and be willing to self-administer a sedative agent to be eligible for enrollment via own informed consent or from a legally authorized representative (LAR). A detailed description of the parent clinical trial and its protocol can be found elsewhere [ 11 ]. All research was performed in accordance with human subjects in research guidelines put forth by Mayo Clinic’s Institutional Review Board (IRB) and the University of Minnesota IRB for greater than minimal risk clinical trials.…”
Section: Methodsmentioning
confidence: 99%